Dialogue between two Chief Worldview Systems on Quantized Orbit Distances as Astrophysics Phenomena (Bulletin of Pure and Applied Sciences – Physics, 2021)
This is a follow-up to our previous paper, suggesting going toward quantum geophysics and  quantum astrophysics. Recently, a colleague asks to this author: “1. What is the quantum  interpretation of the astrophysics? 2. What is the quantum explanation of the orbital  distances?” This review paper will discuss two chief worldview systems on such quantized  orbitdistances as a phenomenon in astrophysics and astronomy. We will discuss in specific  way: scale relativity approach of Prof. Laurent Nottale, in comparison with our own  approach. This short review is also intended as a response to M. Pitkanen’s recent article.1We  hope this discussion will be found interesting.